Upaya Menemukan Konsep Ideal Hubungan Pusat-Daerah Menurut Undang-Undang Dasar Negera Republik Indonesia Tahun 1945 - Muhammad Ridwansyah (Media Syari'ah, 2017)
This study entitled "In search of Ideal Concepts Central-Local Relations According to the Law of the Republic of Indonesia Year 1945". This study aims to determine the future of local governance arrangements relating to the principle of asymmetric decentralization so much more freely take care of his own household. This study is a conceptual attempt to discover the concepts of central and local relations by UUDNRI 1945. The data was collected using library research (literature research) were performed to obtain secondary data in the legal field. This research is descriptive analysis is a study that aims to describe or illustrate a systematic, factual and accurate to a poluasi or a particular region, on the nature or certain factors. Based on the results of the discussion are available, the results of this study are. First, the concept of asymmetric decentralization has long sought its format as a constitutional mandate need further interpretation so really find the ideal concept for the Government of Indonesia. Second, the presence of Law Number 23 Year 2014 on Regional Government is already using the principle of broad autonomy so there keluasaan to manage their own regions. But in the case of researchers working to find a new format, which researchers have to offer is asymmetric decentralization to all areas of Indonesia although it seem difficult but it is if it is done jointly it will be easy to implement. Third, related to asymmetric decentralization to Indonesia has been applied to four areas namely Jakarta, Yogyakarta, Aceh and Papua, but researchers expect in the future Indonesia will be easily made further changes to the Law No. 23 Year 2014 on Regional Government. Fourth, Related to the regional authority which will be a very comprehensive course monitoring methods will be much tighter than before because of the decentralization of government power levels allow to lower or below to determine a number of issues, which they note.